Feminist Ideological Bias in the Interpretation of the Qur'an: Implications for Arabic Language Education - Ruslan, Mohammad (STAI At-Tahdzib Rejoagung Ngoro Jombang, 2024)
Qur’anic interpretation is inevitably influenced by the ideological and epistemological backgrounds of its exegetes. In recent decades, feminist interpretations of the Qur’an have emerged as a response to patriarchal readings that dominate traditional exegesis. Feminist scholars attempt to reconstruct the meaning of certain Qur’anic verses—particularly those perceived as marginalizing women—by employing critical hermeneutics and contextual approaches. This study aims to analyze the forms of ideological bias embedded in feminist interpretations of the Qur’an and explore their implications for Arabic language education, especially in Islamic educational settings. Using a descriptive qualitative approach, the research examines feminist tafsir texts alongside pedagogical literature on Arabic language instruction. Findings reveal that feminist ideological bias often leads to reinterpretations that prioritize gender equality, at times diverging from classical Qur’anic sciences and linguistic principles. In the realm of Arabic education, such biases may affect how teachers and students engage with Qur’anic texts, impacting their understanding of linguistic structures, semantic nuances, and the socio-cultural context of the Arabic language. Consequently, there is a growing need for Arabic language pedagogy that is both critical and contextual, while remaining grounded in authoritative interpretative traditions. This study contributes to the discourse on integrating gender-aware readings without compromising the scholarly integrity of Qur’anic interpretation and language instruction.